2003
DOI: 10.1111/1469-7610.00130
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen, female and stressed: changing patterns of psychological distress over time

Abstract: The increase in levels of psychological distress among young females over this period may be explained by an increase in educational expectations, which together with more traditional concerns about personal identity, appear to have elevated levels of stress, with adverse consequences for mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
200
2
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(239 citation statements)
references
References 27 publications
18
200
2
14
Order By: Relevance
“…Also at school, adolescents experience an increased pressure with increasing age, together with the strengthening of the expectation to perform the socially required sexual role. It is here important to observe, with West and Sweeting [25], that school performance, as well as other sources of stress increasing in this period of life, impact much more on girls' health than on boys'.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also at school, adolescents experience an increased pressure with increasing age, together with the strengthening of the expectation to perform the socially required sexual role. It is here important to observe, with West and Sweeting [25], that school performance, as well as other sources of stress increasing in this period of life, impact much more on girls' health than on boys'.…”
Section: Discussionmentioning
confidence: 98%
“…In fact we know [26] that the quality of the relationship with the father decreases more for girls than for boys. The greater importance given to school performance for girls and a greater contrast between familial and mass media values are also suggested as a possible explanation for this difference [25].…”
Section: Discussionmentioning
confidence: 99%
“…Secular trends in depressive symptoms 9 Finally, several studies have examined whether time trends in psychological problems vary according to socio-demographic factors. Some studies indicate gender differences in time trends of depressive symptoms (Sigfusdottir et al, 2008;West & Sweeting, 2003), while others do not (Collishaw, Maughan, Goodman, & Pickles, 2004). Moreover, no variations in time trends were found in relation to families' socio-economic status or family structure (Collishaw et al, 2010;Maughan et al, 2008), whereas one study did find time trends to vary according to number of children in the family (Maughan et al, 2008).…”
Section: Methodological Issuesmentioning
confidence: 97%
“…Moreover, factors such as potentially higher academic pressure at school (West & Sweeting, 2003) and increased exposure to the Internet may be of importance to explain time trends in depressive symptoms.…”
Section: Spurious Relationshipsmentioning
confidence: 99%
“…With regard to general psychopathology, several studies have revealed that adolescent girls report more symptoms of depression, anxiety, and stress than do boys [43][44][45][46]. Externalizing problems are widely considered more prevalent in boys, and, respectively, internalizing ones in girls [43,[47][48][49][50].…”
Section: Gender Differences In Descriptive Statisticsmentioning
confidence: 99%